SOLAR BASED ELECTRICAL VEHICLE (CAR) MODEL - Sagar M. Ghodake 1, Sarvadnya Dattatray Ambare 2, Manoj Nitin Bagal 2, Sanjay Suresh Ghodake 2, Ashitosh Arjun Karape 2 (International Journal of Innovations in Engineering Research and Technology, 2022)
The idea of this project is to design a solar car that aims to tackle the problems related to pollution and shortage of fuel. A Smart vehicle is the one that takes all our burdens on maintenance of the vehicle while ensuring safety and comfort for the driver and the passengers. Various parameters have to be taken into account while designing such a vehicle. In our design we have divided the whole system into two major divisions namely, Greenhouse gas emission from transportation is one of the major environmental issues and its emission rate is increasing at faster rate. So solar power for transportation can solve this problem. The aim of proposed work is to contribute a technology that supports green energy. Consider a scenario we could use a solar energy to charge electric vehicle that too solar panels are inbuilt in the vehicle, but the next question is whether it is feasible in rainy season. It’s difficult to charge inbuilt solar panels during rainy season. The solution is SPEV is supported with a charging cable that plugs in to the vehicle and into a 230v wall socket. The electric vehicle has a built-in features like security system drive guidance system, route detection, android app support, Wi-Fi, Battery Update supported. The results from our research are analyzed in depth. Hence Solar powered electric vehicle (SPEV) results in pollution less transportation.